How to make disease disappear - Chatterjee, Rangan; Bell, Susan (Photographer) (New York, NY : HarperOne, an imprint of HarperCollinsPublishers, 2018)
A simple, accessible program to promote better health and prevent and reverse disease focuses on making changes in four key areas: food, relaxation, sleep, and movement
Includes bibliographical references (pages 213-219) and index
Keywords: Self-care, Health; Health behavior